Analisis Hukum Pidana Terhadap Praktik Grooming Anak di Media Sosial - Raden Suwito; Artukian Laila (INDO PUBLISHING, 2026)
The rise of social media has shifted the patterns of sexual crimes against children from physical spaces to the digital realm, notably through